Pengukuran Kualitas Layanan Website Jurnal GovITA Untuk Mendukung Tata Kelola Publikasi Ilmiah Digital Modern - Aedah Abd Rahman; Angelie Faatihah Susanto; Dwi Nur Karin; Tsaqif Arkan Samaizar (Governance IT Adoption and Technology Advance, 2026)
This study aims to evaluate the quality of digital services on the GovITA Journal Website Portal using the  WebQual 4.0 model, which encompasses three main dimensions: usability, information quality, and service interaction quality, as well as to analyze users’ satisfaction levels with the portal services. The GovITA Journal Portal plays a strategic role in supporting the scientific publication process; therefore, assessing service quality based on user experience is essential to ensure the effectiveness and credibility of the digital publication system. The study employed a quantitative approach by distributing questionnaires to 50 respondents consisting of authors, reviewers, editors, and journal readers. The research instrument was tested for validity and reliability, and all items were found to be valid and reliable. Descriptive analysis revealed that all three WebQual 4.0 dimensions were classified as high, with mean scores of 4.02 for usability, 4.00 for information quality, and 3.88 for service interaction quality. User satisfaction was also categorized as high, with a mean score of 4.04, indicating that the portal has met users’ needs and expectations. The discussion highlights that information quality and ease of use are the dominant factors contributing to user satisfaction. The study recommends improving aspects of service interaction, particularly system reliability and portal response speed, as well as developing a user experience–based interface to enhance overall website performance. These findings provide important contributions for the management of the GovITA Journal in continuously improving digital service quality and strengthening the portal’s position as a modern and user- friendly scientific publication platform.